Ideal convergence of sequences in neutrosophic normed spaces - Kişi, Ömer; Kişi, Ömer (Ios Press, 2021)
Statistical convergence of sequences has been studied in neutrosophic normed spaces (NNS) by Kirisci and Simsek [39]. Ideal convergence is more general than statistical convergence for sequences. This has motivated us to study the ideal convergence in NNS. In this paper, we study the concept of ideal convergence and ideal Cauchy for sequences in NNS.
Keywords: Neutrosophic Normed Spaced; Ideal Convergence; Ideal Cauchy Sequence; T-Norm; T-Conorm